For king and country: an ideological critical study of covenant in Jeremiah 11:1-17 and Kingship in Jeremiah 22:1-23:8 as examples of cultural violence - Gertzen, Marius (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.